Flux synthesis, crystal structures, and physical properties of new lanthanum vanadium oxyselenides. Issue 19 (26th April 2017) - Peschke, Simon; Gamperl, Lisa; Weippert, Valentin; Johrendt, Dirk
Abstract : New vanadium-oxyselenides exhibit increasing structural complexity, mixed-valent vanadium and antiferromagnetism or metamagnetic transitions. Abstract : The new lanthanum vanadium oxyselenides LaVSe2 O, La5 V3 Se6 O7, La5 V3 Se7 O5, La7 VSe5 O7, and La13 V7 Se16 O15 were synthesized in eutectic NaI/KI fluxes, and their crystal structures were determined using single-crystal and powder X-ray diffraction experiments. LaVSe2 O and La5 V3 Se6 O7 adopt known structure types, whereas La5 V3 Se7 O5, La7 VSe5 O7, and La13 V7 Se16 O15 crystallize in hitherto unknown structure types. The main building blocks of these compounds are chains of edge-sharing VSe6, VSe5 O, and/or VSe4 O2 octahedra, linked together by edge-sharing OLa4 and/or OLa3 V tetrahedra forming fluorite-like ribbons. LaVSe2 O, La5 V3 Se7 O5, and La7 VSe5 O7 contain only V(iii ) ions, whereby La5 V3 Se6 O7 and La13 V7 Se16 O15 contain mixtures of either V(iii )/V(iv ) or V(iii )/V(v ) cations. Magnetic measurements indicate Curie–Weiss paramagnetism and magnetic ordering of the vanadium moments at low temperatures. More precisely, we observe antiferromagnetism for La5 V3 Se6 O7, metamagnetism for La5 V3 Se7 O5, ferromagnetism for La7 VSe5 O7 and a complex magnetic structure for La13 V7 Se16 O15 .